Fulminant Heterotopic Ossification following COVID-19 associated Systemic Inflammatory Response Syndrome: Manifestations in Radiology, Nuclear Medicine, and Clinical Application - Kalbi, Deepak P.; Zamora, Edgar; Hari, Adithya; Chun, Kwang J. (World Journal of Nuclear Medicine, 2025)
Heterotopic ossification (HO) is an unclear etiological trigger that results in diverse extra-skeletal bone formation in muscles and soft tissues. This often results in morbidity and reduced quality of life with pain, contractures, and mobility impairment. We present two patients with HO with a history of severe COVID-19 infection requiring 1-month-long mechanical ventilation. The first patient was found to have progressive stiffening of the right knee and left elbow, with clear demonstration of radiographic findings and active dystrophic calcification by nuclear medicine three-phase bone scan. This report might help aid earlier recognition of symptoms for an effective prevention of this debilitating disease. The other patient was also being treated with severe COVID-19, requiring intensive care unit stay with mechanical ventilation demonstrating progressive development of HO on the follow-up computed tomography (CT) images. While abdominal CT studies were obtained for this patient to evaluate the focal sites for infection, the patient was too ill and unable to undergo a bone scan study.
Keywords: heterotopic ossification; joint pain and stiffness; immobility; osteoporosis